(untitled) (Journal of Surgical Sciences, 2021)
Background: Adenocarcinoma involving the 3rd part of the duodenum (D3) is extremely rare. It is frequently missed on upper gastrointestinal (UGI) endoscopy. The standard treatment is either pancreaticoduodenectomy (PD) or segmental duodenal resection. Case Report: Recently, we encountered a 65-year-old man who presented with weakness, epigastric pain, and occasional vomiting. He was investigated with first line investigations; ultrasound (USG) and UGI endoscopy, which revealed normal findings. The second line of investigations, computed tomography (CT), showed a heterogeneously enhanced irregular circumferential thick walled D3. On the basis of CT findings, UGI endoscopy was done a second time and a biopsy was taken from the suspicious area, but the report came as chronic non-specific duodenitis. A third endoscopy was performed by an experienced endoscopist; a biopsy was taken from the growth; the report came as adenocarcinoma. Duodenal segmental resection was planned. Procedure: the lesser sac was opened; 2nd, 3rd and 4th parts of the duodenum were mobilized. Duodenum was resected at the junction of the 2nd and 3rd parts above and the 3rd and 4th parts below. During upper part resection, the ampulla was injured; papillotomy and ampulloplasty were done. Reconstruction was performed by duodenojejunostomy, and to protect the duodeno-jejunostomy, a gastro-jejunostomy and a jejuno-jejunostomy were additionally performed. Histopathology revealed a moderately differentiated adenocarcinoma, pathological stage pT3NOMO (IIA). All the resected margins were free. The patient recovered uneventfully and was discharged with advice for chemotherapy. Conclusion: Diagnosis of D3 cancer is challenging. Segmental duodenal resection is a good surgical option for distal duodenal carcinoma. Journal of Surgical Sciences (2021) Vol. 25(2) : 41-46